INDONESIA'S COMMUNICATION STRATEGY IN CTI-CFF COOPERATION IN SUPPORTING NATIONAL FOOD SECURITY - Salpidawati; Moh Rifaldi Akbar (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article analyzes Indonesia's communication strategy in the multilateral Coral Triangle Initiative on Coral Reefs, Fisheries, and Food Security (CTI-CFF) cooperation, focusing on strategic communication approaches and environmentally-based digital diplomacy. The CTI-CFF is a crucial platform for Indonesia to build its image as a maritime leader and protector of the region's environment. This research employs a literature review and exploratory content analysis of scientific literature, policy documents, and social media content from relevant institutions, such as the Ministry of Maritime Affairs and Fisheries (MMAF) and the CTI-CFF Regional Secretariat. The findings indicate that Indonesia utilizes the CTI-CFF not only as a policy cooperation instrument but also as a strategic communication medium that combines the framing of environmental and food security issues. The "healthy ocean = safe food" framing is a key narrative used to frame environmental issues within the context of national security. Furthermore, using social media as a digital diplomacy tool demonstrates Indonesia's efforts to expand the influence of environmental communication in a public and participatory manner. This study emphasizes the importance of strategic communication in ecologically based regional cooperation. It opens up opportunities for further research on the effectiveness of digital diplomacy and public engagement in national environmental campaigns.